Andrographolide Promotes Uptake of Glucose and GLUT4 Transport through the PKC Pathway in L6 Cells - Jingya Liao; Ziwei Yang; Yanhong Yao; Xinzhou Yang; Jinhua Shen; Ping Zhao (MDPI AG, 2022)
Glucose transporter 4 (GLUT4) is a membrane protein that regulates blood glucose balance and is closely related to type 2 diabetes. Andrographolide (AND) is a diterpene lactone extracted from herbal medicine Andrographis paniculata, which has a variety of biological activities. In this study, the antidiabetic effect of AND in L6 cells and its mechanism were investigated. The uptake of glucose of L6 cells was detected by a glucose assay kit. The expression of GLUT4 and phosphorylation of protein kinase B (PKB/Akt), AMP-dependent protein kinase (AMPK), and protein kinase C (PKC) were detected by Western blot. At the same time, the intracellular Ca2+ levels and GLUT4 translocation in myc-GLUT4-mOrange-L6 cells were detected by confocal laser scanning microscopy. The results showed that AND enhanced the uptake of glucose, GLUT4 expression and fusion with plasma membrane in L6 cells. Meanwhile, AND also significantly activated the phosphorylation of AMPK and PKC and increased the concentration of intracellular Ca2+. AND-induced GLUT4 expression was significantly inhibited by a PKC inhibitor (Gö6983). In addition, in the case of 0 mM extracellular Ca2+ and 0 mM extracellular Ca2+ + 10 μM BAPTA-AM (intracellular Ca2+ chelator), AND induced the translocation of GLUT4, and the uptake of glucose was significantly inhibited. Therefore, we concluded that AND promoted the expression of GLUT4 and its fusion with plasma membrane in L6 cells through PKC pathways in a Ca2+-dependent manner, thereby increasing the uptake of glucose.